Distribution of Relaxation Times Analysis of High-Temperature PEM Fuel Cell Impedance Spectra - Weiß, Alexandra; Schindler, Stefan; Galbiati, Samuele; Danzer, Michael A.; Zeis, Roswitha (Electrochimica Acta, 2017)
In this study, Distribution of Relaxation Times (DRT) was successfully demonstrated in the analysis of the impedance spectra of High-Temperature Polymer Electrolyte Membrane Fuel Cells (HT-PEMFC) doped with phosphoric acid. Electrochemical impedance spectroscopy (EIS) was performed and the quality of the recorded spectra was verified by Kramers-Kronig relations. DRT was then applied to the measured spectra and polarization losses were separated on the basis of their typical time constants. The main features of the distribution function were assigned to the cell's polarization processes by selecting appropriate experimental conditions. DRT can be used to identify individual internal HT-PEMFC fuel cell phenomena without any a-priori knowledge about the physics of the system. This method has the potential to further improve EIS spectra interpretation with either equivalent circuits or physical models.
CRIS-Team Scopus Importer:2023-08-01
Keywords: Distribution of relaxation times; High-temperature PEM fuel cell (HT-PEMFC); Impedance spectroscopy; Membrane Electrode Assembly (MEA); Polarization losses